Role of Emerging Standards and Technologies in Insurance Sector in India: Exploring the Potential of Emerging Standards and Technologies in the Indian Insurance Sector (Journal of Advances and Scholarly Researches in Allied Education, 2017)
This study examines the benefits and barriers as well as the success factors involved in making the transition to a Web-enabled insurance. Insurance Products suitable for E-commerce-Strategies for insurance companies as well as emerging standards and technologies that create the possibilities about next generation of e-commerce in the insurance industry were discussed and examined. The utilization of the Internet is developing all through the world at a quick pace. While the U.S. still holds the lion's offer of the worldwide market, it is foreseen that this offer will decrease from 36 to 25 by 2005. As anyone might expect, e-insurance is also being grasped all around. The European insurance segment, for instance, has been dynamic in making the progress. Asia also indicates gigantic potential to drive this pattern all inclusive. Around half of residential Chinese insurance companies' Web locales at present offer the capacity to purchase strategies online, while India is driving the route in whatever is left of Asia, with quickly extending development in the insurance industry. In spite of the fact that it has been moderate in receiving internet business, the insurance industry stands to pick up considerably from getting the pace. The phantom of an e-empowered insurance scene is speaking to numerous in the business and the potential advantages to be gathered unquestionable reduction of exchange costs, more aggressive products by fusing the speed, adaptability and intelligent capacities of the net, the development of business sectors by creating more leads and extending markets all the more rapidly at a generally bring down cost consequently expanding incomes, and improvement of venture by growing speculation procedures, as well as opportunities for new and existing mediators.